Association Between Same-Day Discharge Total Joint Arthroplasty and Risk of 90-Day Adverse Events in Patients with ASA Classification of ≥3. (3rd November 2021) - Reddy, Nithin C.; Prentice, Heather A.; Paxton, Elizabeth W.; Hinman, Adrian D.; Lin, Abraham G.; Navarro, Ronald A.
Abstract : Background: Although safety in same-day discharge total joint arthroplasty (TJA) has been reported, findings are limited to healthier patients, specific surgeons, and/or specific institutions. Indications for same-day discharge TJA have expanded to include patients with multiple comorbidities; however, safety in this specific patient population remains unknown. Therefore, we sought to compare the risk of 90-day adverse events in higher-risk patients undergoing same-day discharge versus inpatient TJA. Methods: The Kaiser Permanente Total Joint Replacement Registry was utilized to conduct a cohort study. All patients with an American Society of Anesthesiologists (ASA) classification of ≥3 who underwent primary elective TJA for osteoarthritis from 2017 through 2018 were identified. The risk of 90-day adverse events (i.e., emergency department visits, unplanned readmissions, complications, and mortality) was evaluated with use of propensity score-weighted Cox proportional hazard regression including noninferiority testing with a margin of 1.10. Results: The cohort included a total of 5, 250 patients who underwent total hip arthroplasty and 9, 752 patients who underwent total knee arthroplasty, of whom 1, 742 (33.2%) and 3, 283 (33.7%) had same-day discharge, respectively. Same-day discharge hip arthroplasty was noninferior to an inpatient stay in terms of emergency department visits (hazard ratio [HR], 0.73; 1-sided HR 95% upper bound [UB], 0.84), readmissions (HR, 0.47; 95% UB, 0.61), and complications (HR, 0.63; 95% UB, 0.75); we did not have evidence of noninferiority for mortality (HR, 0.84; 95% UB, 1.97). Same-day discharge knee arthroplasty was noninferior to an inpatient stay in terms of emergency department visits (HR, 0.79; 95% UB, 0.87), readmission (HR, 0.80; 95% UB, 0.95), complications (HR, 0.72; 95% UB, 0.82), and mortality (HR, 0.53; 95% UB, 1.03). Conclusions: We found that same-day discharge TJA did not increase the risk of emergency department visits, unplanned readmissions, and complications compared with an inpatient stay for higher-risk patients, suggesting that it is possible to expand indications for same-day discharge TJA in the hospital setting while maintaining safety. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.